FAKTOR - FAKTOR YANG MEMPENGARUHI PERILAKU PENCEGAHAN ANEMIA GIZI BESI PADA IBU HAMIL DI PUSKESMAS LHOK BENGKUANG TAPAKTUAN TAHUN 2022 - Fahdi, Firdaus; Eyanoer, Putri Chairani; Maulidina Hsb, Putri Sari (Fakultas Kedokteran, Institut Kesehatan Deli Husada Deli Tua, 2025)
The incidence of anemia for pregnant ladies remains excessive in Indonesia. Anemia for pregnant girls is referred to as a capability endangering mom and infant. the primary elements inflicting high anemia in pregnant ladies include bad weight-reduction plan throughout pregnancy, adherence to ingesting low iron tablets and irregularities in following antenatal care (ANC) services. This have a look at aimed to investigate factors associated with anemia prevention conduct for pregnant girls. This study was descriptive take a look at with a pass Sectional technique. The pattern of this examine changed into 32 Pregnant ladies who live inside the location near the Lhok Bengkuang Tapaktuan clinic, South Aceh. This have a look at used the Lemeshow sampling method. The effects of the have a look at the usage of Chi square acquired knowledge degree (p value 0.004), agree with (p fee zero.004), Husband support (p fee zero.004) influential on anemia prevention conduct in pregnant ladies on the Lhok Bengkuang Tapaktuan hospital in South Aceh. primarily based at the consequences of logistic regression exams, the most dominant factor is Husband guide influential by way of 37.28 times, other variables are believe and understanding that may boom anemia prevention behavior by way of 19.ninety one instances. it's far advocated for pregnant ladies to growth and apply information that related to the right time to start taking iron drugs and ANC at an early age of pregnancy. For households have to provide support and motivation for pregnant women to make efforts to save you anemia.